Genetic Association of ACE2 rs2285666 Polymorphism With COVID-19 Spatial Distribution in India - Srivastava, Anshika; Bandopadhyay, Audditiya; Das, Debashurti; Pandey, Rudra Kumar; Singh, Vanya; Khanam, Nargis; Srivastava, Nikhil; Singh, Prajjval Pratap; Dubey, Pavan Kumar; Pathak, Abhishek; Gupta, Pranav; Rai, Niraj; et al. (Frontiers in Genetics, 2020)
Studies on host-pathogen interaction have identified human ACE2 as a host cell receptor responsible for mediating infection by coronavirus (Covid-19). Subsequent studies have shown striking difference of allele frequency among Europeans and Asians for a polymorphism rs2285666, present in ACE2. It has been revealed that the alternate allele (TT-plus strand or AA-minus strand) of rs2285666 elevate the expression level of this gene upto 50%, hence may play a significant role in SARS-CoV-2 susceptibility. Therefore, we have first looked the phylogenetic structure of rs2285666 derived haplotypes in worldwide populations and compared the spatial frequency of this particular allele with respect to the Covid-19 infection as well as case-fatality rate in India. For the first time, we ascertained a significant positive correlation for alternate allele (T or A) of rs2285666, with the lower infection as well as case-fatality ratio among Indian populations. We trust that this information will be useful to understand the role of ACE2 in Covid-19 susceptibility.